ダイ4ジ ナンキョク チイキ カンソク カイヒョウ チョウサ ホウコク - 鈴木, 義男; スズキ, ヨシオ; SUZUKI, Yosio (国立極地研究所, 1961)
P(論文) Introduction Since m/s "SOYA" had reached the ice edge on Dec. 27, 1959 at 65°15'S, 48°35'E, the officers on watch carried out continuous visual ice observations, under the supervision of the navigating officer, until the ship left the ice off Riiser-Larsen Peninsula on Feb. 21, 1960. The items of observation were nearly identical with those of the previous three expeditions. As the ship was not bound with drift ice, several surveying cruises were performed between 33°E and 50°E and eleven oceanographic stations were set up in the region. Miscellaneous observations other than general, for instance, observations on the drift of ice field and icebergs, were also made on occasion. 1. Some comments on ice terminology and recording form Several terms were supplemented to the WMO ice terminology mainly from Russian source. Terms were rearranged and compiled in "A glossary of ice terminology to be used in JARE". An example of supplemented terms is secondary slush, which is a combined conception of melting sludge in Baltic ice code and ledyanaya podushka in Russian terminology. Observed items were nearly identical with those required by the U. S. Hydrographic Office's reporting form. Obtained results were compiled in ice charts. Notations used in charts were also similar to those of the U. S. Hydrographic Office. However, the following changes were made both in observed items and in chart notations in order to describe encountered ice conditions more adequately: a) The size of predominant floes was recorded by nearest meters as the index of mechanical decaying. The item "puddling" seems to be insufficient to describe the dacaying state of Antarctic drift ice which decays mechanically before puddles have developed on it. Another index of mechanical decaying such as whether floes have angular or smooth outlines should have been recorded. b) Inter-ice melting sludge was excluded from the first group in the item "concentration by size" and its existence was indicated by a prefix Sl. Though it is difficult to ...